Validation and application of a membrane filtration evaluation protocol for oil-water separation - Mashael Al-Maas (14152386) (2021)
Membrane filtration processes like microfiltration (MF) and ultrafiltration (UF) are proven to be effective in industrial wastewater treatment, including oil-water separation, as they generate suitable quality permeate for water reuse applications. Various research efforts have been conducted in areas of developing and/or modifying commercial MF/UF membrane materials through synthesizing new advanced polymers that promise improvement in oil-water separation performance. Although multiple MF/UF testing procedures were developed, there is still a gap in literature on having a comprehensive protocol that assesses the performance of the membranes in terms of flux, rejection, fouling, and cleanability. This paper delivers a robust bench scale testing procedure incorporating experiences and lessons learned from literature. The evaluation procedure includes three main testing steps: initial characterization, operating performance, and cleaning and recovery. The protocol was designed to mimic industrial conditions by using a representative synthetic produced water solution and operating multiple consecutives cycles of oil-water filtration followed by membrane chemical cleaning. The procedure was initially validated on multiple commercial MF/UF membranes having different pore sizes/MWCOs and chemistries obtained from various manufacturers and then applied to evaluate emerging membrane materials. The protocol was found to be reliable in evaluating the performance trends of various commercial membranes and effective in comparing the performance of emerging membranes. The developed procedure is proposed to be applied by researchers to assess the performance of new membrane materials as compared to relevant commercial products. Other Information Published in: Journal of Water Process Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jwpe.2021.102185